Neurotourism Insights: Eye Tracking and Galvanic Analysis of Tourism Destination Brand Logos and AI Visuals - Víctor Calderón-Fajardo; Rafael Anaya-Sánchez; Francisco Rejón-Guardia; Sebastian Molinillo (Tourism & Management Studies)
This pioneering study explores the intersection between Neurotourism, defined as the integration of neurosciences in tourism, and the perception of tourism Brand Personality (BP) through the advanced use of psychophysiology techniques, specifically Eye-Tracking (ET) and Galvanic Skin Response (GSR). It analyses how tourism destination brand logos/combination marks and images generated by artificial intelligence (AI) influence consumer attention and emotional response. Focusing on the five dimensions of BP proposed by Aaker (1997) - sincerity, excitement, sophistication, competence, and ruggedness - this study highlights significant differences in how men and women process and react to brand values associated with specific cities. Employing a rigorous methodological approach and the application of non-parametric statistical analyses, the findings reveal distinct patterns of visual attention and emotional responses across genders, emphasising the importance of considering BP in the marketing and design of tourism destination brand logos/combination marks. This work not only advances theoretical understanding of tourist consumer behaviour but also offers relevant practical implications for tourism marketing and destination management.